Wasatiya in international diplomacy: An analysis of the application of moderation in addressing global conflicts - Nayab, Syade Dur e; Zarei, Mohammad Javad (Arshaka: Social Sciences and Education, 2025)
This article aims to analyze the application of the Wasatiya principle as a diplomatic strategy in resolving global conflicts, focusing on the implementation of moderation in international diplomacy. The method used is a descriptive literature review, with data sourced from international journals indexed in Scopus or DOAJ (2015-2024). The research findings indicate that the Wasatiya moderation principle is effective in reducing international tensions, creating an inclusive dialogue space, and achieving peaceful solutions. The application of this principle allows for the creation of an inclusive and constructive dialogue space, while avoiding confrontations that exacerbate conflicts. However, the main challenges faced include mistrust between countries and the imbalance of power in global diplomacy. These findings suggest that, despite these obstacles, the Wasatiya principle remains relevant and effective in creating sustainable peace in international diplomacy by promoting inclusivity and fair solutions for all parties involved.